The Influence of The Whatsapp Application On Students' Ability to Write Procudure Texts - Huda, Rahmat; Lestari, Nida (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The problem formulation in this research is